Integrated innovation strategies on sustainability of agricultural cooperatives in Lejweleputswa district, Free State Province, South Africa - Gantsho, Siyaze Knowledge (University of the Free State, 2023)
Agriculture is practiced in rural areas characterised by extreme poverty. In the Lejweleputswa district, crop farming cooperatives, together with other agricultural production activities, are significant economic engine. Conversely, modern crop producers are reluctant to incorporate innovation into their routine farming practices. This paper, which focuses on integrated innovation methods that support agricultural cooperatives, is a component of a PhD research project conducted in the province of Free State in the Lejweleputswa district municipality. The lack of enthusiasm among cooperative members in integrating innovation techniques into business operations as a trending factor for sustainability made agriculture cooperatives unsustainable, according to the study's research topic. The primary objective was to examine the impact of integrated innovation strategies on the sustainability of agriculture cooperatives in Lejweleputswa district, Free State province in order to make a policy recommendation for sustainability. The descriptive study analysis was conducted on 139 cooperative members from 25 different agriculture cooperatives. Data was collected using survey questions that were standardised. Likert scales with 5 points were used to assess these survey questions. Collected data sets were analysed using SPSS version 28 software. The data was found to be reliable as a Cronbach’s alpha was found to be 0.927 and 0.861 for product and process innovation strategy implementation. The average correlation coefficient was observed to be 0.6 which denotes an overall positive correlation between variables. The one sample test was used to determine the p-value (Sig-value), which was found to be less than 0.05. Pearson correlation coefficient was found to be 0.68 on average, denoting that there is a positive relationship between variables of organisational strategies. The p-value (0.026) < 0.05 indicated a statistically significant difference between the variables. The F-value for marketing innovation strategies variables was found to be less than the degree of freedom, 1.552 and 3.0, respectively. Thus, the hypothesis was accepted. The one-sample t test was also used to determine the mean, standard deviation, and the p-values of the results. All the mean values were significantly higher than 3, and p-values were found to be all less than 0.05, thus indicating that respondents agree with the discussed challenges. The findings indicated that RSMEA, NNFI and CFI were within the acceptable ranges for good model fit at 0.049, 0.953 and 0.957, respectively. This implies that the hypothesised model was a good fit for collected data. It was observed that only 40.29% agreed to have received financial support from FDI’s and only 58.27% agreed to have received non-financial support from government agencies. The results suggest that agricultural cooperatives are not motivated to use innovative marketing techniques. It is determined that most the Lejweleputswa district's agricultural cooperatives have a poor opinion of marketing innovation. The result of the study proves the hypothesis that the implementation of innovation strategies is significantly low in agriculture cooperatives.

Landbou word meestal beoefen in landelike gebiede wat gekenmerk word deur uiterste armoede. In die Lejweleputswa-distrik vorm koöperasies geskik vir saaiboerdery, tesame met ander landbouproduksie-aktiwiteite, ’n belangrike dryfkrag vir die plaaslike ekonomie. Nietemin is moderne gewasprodusente huiwerig om innovasie in hul roetineboerderypraktyke te integreer. Hierdie studie, wat fokus op geïntegreerde innovasiemetodes ter ondersteuning van landboukoöperasies, vorm deel van ’n PhD-navorsingsprojek wat in die Vrystaat Provinsie, binne die Lejweleputswa-distriksmunisipaliteit, uitgevoer is. Die gebrek aan entoesiasme onder koöperasielede om innovasietegnieke in hul besigheidsbedrywighede te integreer, is volgens die navorsing ’n bepalende faktor wat die volhoubaarheid van landboukoöperasies benadeel. Die primêre doel was om die invloed van geïntegreerde innovasiestrategieë op die volhoubaarheid van landboukoöperasies in die Lejweleputswa-distrik, Vrystaat, te ondersoek, met die oog daarop om beleidsaanbevelings vir volhoubaarheid te formuleer. ’n Beskrywende studie-analise is uitgevoer op ’n steekproef van 139 koöperasielede afkomstig uit 25 verskillende landboukoöperasies. Data is ingesamel deur middel van gestandaardiseerde opnamevrae. Die vrae is geëvalueer aan die hand van vyfpunt-Likertskale. Die ingesamelde data is ontleed met behulp van SPSS-weergawe 28-sagteware. Die betroubaarheid van die data is bevestig met Cronbach se alfa-waardes van onderskeidelik 0,927 en 0,861 vir produk- en proses-innovasiestrategie-implementering. Die gemiddelde korrelasiekoëffisiënt van 0,6 dui op ’n oorwegend positiewe verband tussen veranderlikes. Die eensteekproeftoets is gebruik om die p-waarde (Sig-waarde) te bepaal, wat laer as 0,05 was. Die Pearson-korrelasiekoëffisiënt is gemiddeld op 0,68 bepaal, wat op ’n positiewe verband tussen organisasiestrategieveranderlikes dui. Die p-waarde (0,026) < 0,05 het ’n statisties beduidende verskil tussen die veranderlikes aangedui. Die F-waarde vir bemarkingsinnovasiestrategie-veranderlikes is op 1,552 bepaal, teenoor die vryheidsgrade van 3,0 en was dus laer. Die hipotese is gevolglik aanvaar. Die eensteekproef t-toets is verder gebruik om die gemiddelde, standaardafwyking en p-waardes van die resultate te bereken. Alle gemiddelde waardes was beduidend hoër as 3, terwyl alle p-waardes laer as 0,05 was – wat daarop dui dat respondente saamstem met die geïdentifiseerde uitdagings. Die bevindings toon dat “RSMEA”, “NNFI” en “CFI” binne die aanvaarbare omvang vir goeie modelpassing was, naamlik 0,049, 0,953 en 0,957 onderskeidelik. Dit impliseer dat die veronderstelde model goed by die ingesamelde data gepas het. Slegs 40,29% van die respondente het aangedui dat hulle finansiële steun van direkte buitelandse beleggings ontvang, terwyl 58,27% nie-finansiële steun van staatsinstansies ontvang. Die resultate dui aan dat landboukoöperasies nie gemotiveerd is om innoverende bemarkingstegnieke aan te wend nie. Daar is verder vasgestel dat die meeste landboukoöperasies in die Lejweleputswa-distrik ’n negatiewe persepsie van bemarkingsinnovasie het. Die resultate bevestig die hipotese dat die implementering van innovasiestrategieë in landboukoöperasies beduidend laag is.

Temo e etswa dibakeng tsa mahaeng tse khethollwang ke bofutsana bo feteletseng. Seterekeng sa Lejweleputswa, dikoporasi tsa temo ya dijalo, hammoho le mesebetsi e meng ya tlhahiso ya temo, ke sesosa sa bohlokwa sa moruo. Ka lehlakoreng le leng, bahlahisi ba kajeno ba dijalo ha ba rate ho kenyeletsa mekgwa e metjha mesebetsing ya bona e tlwaelehileng ya temo. Pampiri ena, e shebaneng le mekgwa e kopantsweng ya boiqapelo e tshehetsang dikoporasi tsa temo, ke karolo ya projeke ya diphuputso tsa PhD tse entsweng provenseng ya Freistata ho Masepala wa setereke sa Lejweleputswa. Ho ya ka sehlooho sa diphuputso, ho haella ha tjheseho hara ditho tsa dikgwebo tsa tshebedisano ho kenyeletsa mekgwa ya ho qapa mesebetsing ya kgwebo e le tshusumetso ya ho tsitsa ho entseng hore dikgwebo tse sebedisanang hammoho tsa temo di se ke tsa tsitsa. Sepheo se ka sehloohong e ne e le ho hlahloba phello ya maano a kopantseng a ho qapa mekgwa e metle mabapi le ho tsitsa ha dikgwebo tsa temo seterekeng sa Lejweleputswa, provenseng ya Freistata e le ho etsa tlhahiso ya leano bakeng sa botsitso. Tlhahlobo ya thuto e hlalosang e ile ya etswa ho ditho tsa tshebedisanommoho tse 139 tse tswang ho dikgwebo tse kgolo tse 25 tse fapaneng tsa temo. Dintlha di ile tsa bokellwa ka dipotso tse tlwaelehileng tsa diphuputso. Ho ile ha sebediswa sekala sa Likert se nang le dintlha tse 5 ho hlahloba dipotso tsena tsa diphuputso. Dintlha tse bokeleditsweng di ile tsa hlahlojwa ho sebediswa softewere ya SPSS version 28. Dintlha di ile tsa fumanwa di tshepahala kaha alpha ya Cronbach e ile ya fumanwa e le 0.927 le 0.861 bakeng sa ho sebedisa leano la ho ntjhafatsa sehlahiswa le tshebetso. Ho ile ha hlokomelwa hore karolelano ya kgokahano e ne e le 0, 6 e bontshang kgokahano e ntle ka kakaretso pakeng tsa dintlha tse fapaneng. Ho ile ha sebediswa teko ya sampole e le nngwe ho fumana boleng ba p (Sig-value), e ileng ya fumanwa e le ka tlase ho 0,05. Pearson correlation coefficient e ile ya fumanwa e le 0.68 ka karolelano, e bontshang hore ho na le kamano e ntle pakeng tsa mefuta e sa tshwaneng ya mekgwa ya mokgatlo. P-value (0. 026) < 0. 05 e bontshitse phapano ya bohlokwa dipalopalo pakeng tsa mefuta e sa tshwaneng. Ho ile ha fumanwa hore F-value bakeng sa mekgwa ya ho rekisa e ne e le tlase ho tekanyo ya tokoloho, 1.552 le 3.0, ka ho latellana. Kahoo, kgopolotaba eo e ile ya amohelwa. Teko ya t ya sampole e le nngwe e ne e boetse e sebedisetswa ho fumana karolelano, ho kgeloha ho tlwaelehileng le ditekanyetso tsa p tsa diphetho. Ditekanyetso tsohle tse bohareng di ne di phahame haholo ho feta 3, mme ho ile ha fumanwa hore ditekanyetso tsa p kaofela di ka tlase ho 0,05, ka hona di bontsha hore ba arabetseng ba dumellana le mathata a tshohlwang. Diphuputso di bontshitse hore RSMYA, NNFI le CFI di ne di le ka hara meedi e amohelehang bakeng sa mohlala o loketseng hantle ho 0,049, 0,953 le 0,957, ka ho latellana. Sena se bolela hore mohlala oo ho neng ho nahanwa ka wona o ne o dumellana hantle le boitsebiso bo bokelletsweng. Ho ile ha hlokomelwa hore ke ba 40.29% feela ba ileng ba dumela hore ba fumane tshehetso ya ditjhelete ho tswa ho FDIhs mme ke ba 58.27% feela ba ileng ba dumela hore ba fumane tshehetso eo eseng ya ditjhelete ho tswa mekgatlong ya mmuso. Diphetho di fana ka maikutlo a hore mekgatlo ya tshebedisano ya temo ha e susumelletsehe ho sebedisa mekgwa e metjha ya ho rekisa. Ho fumanwe hore boholo ba mekgatlo ya tshebedisano ya temo ya setereke sa Lejweleputswa e na le maikutlo a fosahetseng mabapi le ho bapatsa boqapi. Phello ya thuto e paka kgopolo ya hore ho sebediswa ha maano a ho ntjhafatsa, ho tlase haholo dikhamphaning tsa temo.

Ezolimo ziyenzeka ezindaweni zasemaphandleni zichazwa ngobubha obusezingeni eliphakeme. Esifundeni saseLejweleputswa, imifelandawonye yezolimo lwezitshalo, kanye neminye imisebenzi yemikhiqizo yezolimo, kuyizinjini zezomnotho ezibaluleke kakhulu. Okuphikisana nalokho, abakhiqizi bezitshalo besimanje banokungabaza ukubandakanya izinto ezintsha endleleni yabo yomsebenzi wokulima. Leli phepha, ligxile ekubandakanyeni izindlela ezintsha ezelekelela imifelandawonye yezolimo, liyingxenye yomsebenzi wocwaningo lwe-PhD owenziwa ezifundazweni saseFree State kumasipala wesifunda saseLejweleputswa. Ukungabi bikho kokugqugquzeleka phakathi kwamalunga omfelandawonye ekusebenziseni amasu ezinto ezintsha emisebenzini yebhizinisi kuyisici esisabalele ekusimemeni okwenziwa imifelandawonye yezolimo engasimeme, ngokwesihloko socwaningo. Inhloso enkulu kwakungukuhlola umthelela wamasu ezinto ezintsha ebandakanyiwe ekusimamiseni imifelandawonye yezolimo esifundeni saseLejweleputswa, esifundazweni saseFree State ukuze kwenze isincomo senqubomgomo ukwenzela ukusimama. Ukuhlaziya ucwaningo oluchazayo kwenziwa ngamalunga omfelandawonye ayi-139 kusuka emifelandawonyeni yezolimo eyehlukene engama-25. Imininingo yaqoqwa ngokusebenzisa imibuzo yesaveyi. Imininingo eyaqoqwa yahlaziywa ngokusebenzisa uhlobo lwesofthiwe yohlobo lwe-SPSS, imininingo yatholakala ingethembekile njengoba iCronbach’s alpha yatholakala ingu-0.927 kanye no-0.861 emkhiqizweni kanye nasenqubeni yokusebenzisa amasu okusungula izinto ezintsha. Inombolo esiza ukubona ukuhlobana kwezinto elindelekile yabonakala iwu-0.6 nechaza ukuhloba okuhle okuphelele phakathi kamavarebuli. Isivivinyo esisodwa sokusampula sasetshenziswa ukuhlonza i-p-value (Sig-value), nokwatholakala ukuthi kwakungaphansi kwa-0.05. inombolo esiza ukubona ukuhlobana kwezinto kaPearson yatholakala iwu-0.68 ngokulindelekile, okuchaza ukuthi kunobudlelwano obuhle phakathi kwamavarebuli amasu enhlangano. I-p-value (0.026) < 0.05 yaveza umehluko omkhulu wezinombolo phakathi kwamavarebuli. I-F-value yamavarebuli amasu amasha ezimakethe yatholakala ingaphansi kwezinga lenkululeko, u-1.552 kanye no-3.0, ngokuhlukana kwakho. Okusho ukuthi-ke, isihlawumbiselo sasemukelekile. Isivivinyo se-t sesampula eyodwa naso sasetshenziswa ukuhlonza imini (mean), ukwehluka okwejwayelekila, kanye nama-p-values emiphumela. Wonke amanani emini (mean) ayemakhulu kakhulu ngaphezu kuka-3, futhi ama-p-values atholaka wonke engaphansi kuka-0.05, lokho okukhomba ukuthi abahlanganyeli bayavumelana nezingqinamba okuxoxwe ngazo. Imiphumela yaveza ukuthi i-RSMEA, i-NNFI kanye ne-CFI yayisezingeni elamukelekayo yokusebenza kahle kwemodeli ku-0.049, 0.953 naku-0.957, ngokwehlukana kwakho. Lokhu kuchaza ukuthi imodeli ehlawumbiseliwe yayizosebenza kahle ukuqoqa imininingo. Kwabonakala ukuthi abangama-40.29% kuphela abavuma ukuthi bayaluthola uxhaso lwezezimali oluphuma ku-FDI kanti abangama-58.27% bavuma ukuthi babengalutholi uxhaso lwezimali ezithunyweni zikahulumeni. Imiphumela iphakamisa ukuthi imifelandawonye yezolimo ayinakugqugquzeleka ukusebenzisa amasu amasha ezezimakethe. Kuyatholakala ukuthi imifelandawonye yezolimo yesifunda saseLejweleputswa inombono engeyinhle yokuthuthukisa izimakethe. Umphumela walolu cwaningo uyasiqinisekisa isihlawumbiselo sokuthi ukusetshenziswa kwamasu okusungula izinto ezintsha kuphansi kakhulu kumifelandawonye yezolimo.
Geïntegreerde innovasiestrategieë vir die volhoubaarheid van landboukoöperasies in die Lejweleputswa-distrik, Vrystaat Provinsie, Suid-Afrika
Mawala a matjha a kopaneng bakeng sa tswelopele ya dikgwebo tsa temothuo seterekeng sa Lejweleputswa, Provenseng ya Freistata, Afrika Borwa
Thesis (Ph.D.(Sustainable Agriculture))--University of the Free State, 2023
Keywords: Integrated innovation strategies; Sustainability of agricultural cooperatives; Agricultural cooperatives; Lejweleputswa District Municipality, South Africa; Geïntegreerde innovasiestrategieë; Volhoubaarheid van landboukoöperasies; Landboukoöperasies; Lejweleputswa-distriksmunisipaliteit; Suid-Afrika; Landboukoöperasies; Mawala a matjha a kopaneng; Tswelopele ya dikgwebo tse kgolo tsa temothuo; Dikgwebo tse kgolo tsa Temothuo; Masepala wa Setereke sa Lejweleputswa; Afrika Borwa; Amasu okusungula izinto ezintsha; Ukusimamisa imifelandawonye yezolimo; Imifelandawonye yezolimo; UMasipala wesiFunda saseLejweleputswa; eNingizimu Afrikha